CD4+ T Helper Cells Play a Key Role in Maintaining Diabetogenic CD8+ T Cell Function in the Pancreas - Espinosa-Carrasco, Gabriel; Le Saout, Cécile; Fontanaud, Pierre; Stratmann, Thomas; Mollard, Patrice; Schaeffer, Marie; Hernandez, Javier (Frontiers in Immunology, 2018)
Autoreactive CD8+ and CD4+ T cells have been assigned independent key roles in the destruction of insulin-producing beta cells resulting in type 1 diabetes. Although CD4 help for the generation of efficient CD8+ T cell responses in lymphoid tissue has been extensively described, whether these two cell populations cooperate in islet destruction in situ remains unclear. Using intra-vital 2-photon microscopy in a mouse model of diabetes, we visualized both effector T cell populations in the pancreas during disease onset. CD4+ T helper cells displayed a much higher arrest in the exocrine tissue than islet-specific CD8+ T cells. This increased arrest was MHC class II-dependent and locally correlated with APC recruitment. CD8+ T cells deprived of continued CD4 help specifically in the pancreas, through blocking MHC class II recognition, failed to maintain optimal effector functions, which contributed to hamper diabetes progression. Thus, we provide novel insight in the cellular mechanisms regulating effector T cell functionality in peripheral tissues with important implications for immunotherapies.